2005
DOI: 10.1111/j.1600-051x.2005.00705.x
|View full text |Cite
|
Sign up to set email alerts
|

Root surface removal and resultant surface texture with diamond‐coated ultrasonic inserts: an in vitro and SEM study

Abstract: These results suggest that diamond-coated ultrasonic instruments will effectively plane roots, and that caution should be used during periodontal root planing procedures. Additionally, the diamond-coated instruments will produce a rougher surface than the plain inserts or the hand curettes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
1
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 54 publications
2
39
1
3
Order By: Relevance
“…The hand instrumentation showed similar defect depth to that produced by the ultrasonic scaler. In a SEM evaluation, Vastardis et al (12) did not find any difference between these two forms of root instrumentation with regard to the defect depth, although other studies have reported less root substance removal by ultrasonic scalers compared to hand instruments (1,4). However, in a recent study, the piezoelectric scalers removed less root substance than hand curettes (13).…”
Section: Discussionmentioning
confidence: 77%
“…The hand instrumentation showed similar defect depth to that produced by the ultrasonic scaler. In a SEM evaluation, Vastardis et al (12) did not find any difference between these two forms of root instrumentation with regard to the defect depth, although other studies have reported less root substance removal by ultrasonic scalers compared to hand instruments (1,4). However, in a recent study, the piezoelectric scalers removed less root substance than hand curettes (13).…”
Section: Discussionmentioning
confidence: 77%
“…In fact, the effects of different periodontal instruments on the root surface roughness have often been investigated over the years and conflicting results have been found. Some investigations demonstrated no difference in the roughness of surfaces treated with either curettes or ultrasonic instruments 22 ; others demonstrated that the smoothest surfaces were produced by hand instruments 23,24 or by ultrasonic instruments. 25 With regard to the use of the Er:YAG laser, a previous investigation 12 found no differences in root surface roughness following Er:YAG laser irradiation and treatment with curettes.…”
Section: Discussionmentioning
confidence: 99%
“…The Ra value of the root surface has been reported to be in the range of 0.41–1.12 µm [4]. Various methods of root planing have been reported to produce a root surface roughness in the range of 0.35–4.90 µm depending on the instruments used [451314]. The plates with an Ra value corresponding to a high-nanometer dimension (867.0±168.6 nm) and a mid-nanometer dimension (505.3±115.3 nm) were rougher than the enamel surface and within the range of the Ra reported on the untreated root surface or the root surface after root planing.…”
Section: Methodsmentioning
confidence: 99%